Toxic effects of antineoplastic therapy in patients breast cancer in Caruaru-PE oncology center - Rayssa Almeida-Carneiro; Ana Caroline de-; Sabryna Aleadynah Barbosa-; Iago Dillion Lima-Cavalcanti; Analúcia Guedes Silveira-Cabral; Adrya Lucia Peres
ABSTRACT Objective: to evaluate the main clinical symptoms associated with the toxic effects of antineoplastic therapy in women with breast cancer at a cancer treatment center in the city of Caruaru/PE. Methods: This is an analytical and transversal study with a quantitative approach, carried out between September and December 2017, whose data source was the medical records of the patients included in the study. Results: the majority of the sample consisted of women aged between 41 and 50 years (28.6%). This study made it possible to identify the most frequent histological type of breast cancer, with invasive ductal carcinoma observed in 88.6% and the most used protocol was Doxorubicin, Cyclophosphamide and Paclitaxel. Alopecia (91.4%) was the main adverse event observed in patients. Conclusion: it was possible to verify that the observation of these effects, allows a better control during the therapy, enabling improvement of the time and quality of life.